Survival and desferrioxamine in thalassaemia major. Issue 6322 (10th April 1982) - Modell, B; Letsky, E A; Flynn, D M; Peto, R; Weatherall, D J
Abstract : A small randomised trial and observation of all patients homozygous for beta-thalassaemia in Britain born in or before 1963 indicated that those patients who had received average weekly doses of more than 4 g of desferrioxamine over the previous few years were less likely to die in the near future than were patients of similar ages who had received less, or no, desferrioxamine.